Penerapan Metode SQ3R untuk Meningkatkan Hasil Belajar Siswa pada Pemahaman Membaca Cerita Mata Pelajaran Bahasa Indonesia di Kelas IV MI Cibuntu Bogor - Nurkaidah Nurkaidah (EduInovasi: Journal of Basic Educational Studies, 2023)
Understanding literacy in grade 4 is already a very important part. If you still find many students whose ability to understand the meaning of their reading is poor, it will greatly affect the process of self-development of students and the learning process in class. The ability to understand reading has a big impact on all subjects so that it affects student learning outcomes. The research objective was to improve learning outcomes and reading comprehension using the SQ3R method for fourth grade students MI Cibuntu. This type of research is Classroom Action Research (CAR). Where the teacher as the executor of learning while the researcher as an observer. The research design uses the Kemmis and Mc. Taggart. The subjects of this study were students of class IV MI Cibuntu which consisted of 30 students. The object of research is the result of learning reading comprehension. Data collection techniques using observation and interviews. Data were analyzed descriptively and presented in tabular form. The results showed that there was an increase in reading comprehension learning outcomes, namely in the first cycle by 69% (enough category), then in the second cycle it increased to 82% (very good category). This means an increase of 13%. Thus the use of the SQ3R (Survey, Question, Read, Recite, Review) method in Indonesian subjects can improve learning outcomes in reading comprehension for class IV MI Cibuntu Bogor. Keywords: Learning Outcomes, SQ3R Method, Reading comprehension